The Role of CT Guidance in T2–T3 Sympathetic Block: Overindulgence or Essential Safety Measure? - Kanchan Godase; Nivedita Page; Kashinath Bangar; Charusheela Gaikwad (Indian Journal of Pain)
Pain management is crucial in health care, especially in India where chronic pain affects millions of individuals. This case report discusses a rural woman with left finger gangrene unresponsive to medical management. She was planned for computed tomography (CT)- guided T2–T3 sympathetic block but was deferred due to incidental finding of pericardial effusion. Further evaluation revealed that she had systemic lupus erythematosus (SLE). She was subsequently managed with an ultrasound-guided stellate ganglion block. This case outlines the importance of thorough preprocedural evaluation and highlights the advantages of CT guidance in preventing complications and facilitating proper intervention.